Towards a Higher Comparability of Geothermometric Data Obtained by Raman Spectroscopy of Carbonaceous Material. Part 2: A Revised Geothermometer. Issue 4 (26th July 2017) - Lünsdorf, N. Keno; Dunkl, István; Schmidt, Burkhard C.; Rantitsch, Gerd; von Eynatten, Hilmar
Abstract : The estimation of the peak metamorphic temperature by Raman spectroscopy of carbonaceous material (RSCM) is influenced by several bias sources grouped in measuring conditions, spectral processing and sample heterogeneity. The measuring conditions (selected excitation wavelength) and the operator bias during spectral processing have a pronounced impact on the temperature estimate and thus on the comparability and portability of thermometric data obtained by RSCM. Several calibration lines of RSCM geothermometers are published already, but no standardised approach exists. Samples of carbonaceous material bearing metasediments with well‐established metamorphic conditions of the central and western Alps compile a reference series. By applying an automated, iterative and randomised curve‐fitting approach, a consistent and user input‐independent RSCM geothermometer is presented, which covers peak metamorphic temperatures from ca . 160 to 600 °C. The method is hardware independent because the measuring conditions bias is excluded by the use of the reference series and the automated curve‐fitting approach reduces the spectral processing bias effectively, increasing the method's comparability and portability. By distributing the reference series and the automated curve‐fitting software, a laboratory will be able to derive a laboratory specific calibration line for the RSCM geothermometer. Key Points: Based on a novel evaluation scheme and a reference series a standardized methodology to RSCM geothermometry is presented. The Scaled Total Area (STA)‐RSCM approach will increase the comparability of RSCM geothermometric data. The STA‐RSCM approach provides a continuous geothermometer from ca . 160 to 600 °C